The Reimagining of The Western-Centric Savior Myth as a Superhero: The Use of Masks in The Dark Knight Film - Çelik, Kemal (My University, 2023)
Masks have been used throughout human history as objects with significant symbolic value, despite their simple materials such as fabric or wood. Masks have the ability to convey meanings beyond what is visible, allowing the wearer to assume a second identity represented by the mask, which can be independent from their own human identity and even drastically different. This study examines the use of masks as a means of expression, focusing on the superhero film The Dark Knight (2008), using a mixed methodology approach. As evident from the article, the film features three primary masks: Batman's mask representing global power and authority employed by capitalism, Joker's mask representing chaos and anarchy, and Dent's mask symbolizing the ordinary human. While the first two mask uses are elevated in the film's language, the utilization of the mask representing the human face is portrayed as insignificant. Consequently, the film implies that to be accepted as a savior, one must transcend their humanity and assume a transhuman form.
Keywords: Identity; Power; Ideology; Mask; Superhero